Resin Composite
The resin composite, featuring a resin foam core and a fiber-reinforced resin layer, addresses the challenge of balancing bending rigidity and light weight by optimizing modulus ratios and density, resulting in a composite that effectively meets both requirements.
Patent Information
- Application Number
- JP2022043905
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-03-18
- Publication Date
- 2025-04-14
- Estimated Expiration
- 2042-03-18
AI Technical Summary
Existing resin composites struggle to achieve a balance between bending rigidity and light weight, often requiring thicker fiber-reinforced resin layers which can compromise the foaming degree of the resin foam, leading to insufficient lightness.
A plate-like resin composite is designed with a core material made of resin foam and a surface material comprising a fiber-reinforced resin layer. The composite satisfies specific modulus ratios and density relationships to optimize bending rigidity and light weight.
The resin composite achieves a balance between bending rigidity and light weight, meeting the demands for both properties effectively.
Smart Images

Figure 0007661265000003 
Figure 0007661265000004 
Figure 0007661265000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composite, and more specifically, to a resin composite including a core material and a surface material covering the core material, the core material being composed of a resin foam, and the surface material including a fiber-reinforced resin layer composed of a sheet-like fiber-reinforced resin material containing a resin and fibers. [Background technology]
[0002] Conventionally, fiber-reinforced resin materials, such as FRP, have been widely used because they combine excellent lightness and strength. In recent years, resin composites in which a surface material including a fiber-reinforced resin layer is laminated on a resin foam as a core material have expanded their applications. This type of resin composite exhibits excellent lightness by having a resin foam as a core material. In addition, since the fiber-reinforced resin layer is composed of a fiber-reinforced resin material containing fibers and resin, a resin composite that includes a fiber-reinforced resin layer as a surface material and is excellent in terms of strength is described in the following Patent Document 1, which describes a resin composite with excellent bending rigidity in the longitudinal direction. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2000-343476 A Summary of the Invention [Problem to be solved by the invention]
[0004] In order to improve the bending rigidity of a resin composite that is a plate-shaped body having a longitudinal direction and a lateral direction, it is necessary to thicken the fiber-reinforced resin layer or reduce the foaming degree of the resin foam, which may result in insufficient light weight. It is difficult to say that the demand for a plate-shaped resin composite that can achieve both bending rigidity and light weight has been fully met. Therefore, an object of the present invention is to provide a plate-shaped resin composite that can achieve both bending rigidity and light weight. [Means for solving the problem]
[0005] In order to solve the above problems, the present invention provides A core material and a surface material covering the core material, The core material is made of a resin foam, The surface material is a resin composite including a fiber reinforced resin layer composed of a sheet-shaped fiber reinforced resin material containing resin and fibers, A plate-like body having a longitudinal direction and a lateral direction perpendicular to the longitudinal direction, The tensile modulus of the fiber reinforced resin layer in the longitudinal direction is Ew (GPa), The tensile modulus of the fiber reinforced resin layer in the short direction is Eh (GPa), The tensile modulus of the core material in the longitudinal direction is Ef (MPa), The apparent density of the core material is D (kg / m 3 ), then A resin composite is provided that satisfies all of the following formulas (1), (2), and (3): 6 ≦ (Ew / Eh) ≦ 20 ···(1) 70 ≦ Ew (2) 0.5 ≦ (Ef / D) ≦ 1.5 (3) Effect of the Invention
[0006] According to the present invention, a plate-shaped resin composite material that is both highly flexible and lightweight can be provided. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a schematic perspective view showing a resin composite of one embodiment. [Diagram 2] FIG. 2 is a cross-sectional view of the resin composite (a cross-sectional view taken along line II-II in FIG. 1). [Figure 3A] FIG. 3A is an enlarged cross-sectional view of a surface layer portion of the resin composite (an enlarged view of part III in FIG. 2). [Figure 3B]FIG. 3B is an enlarged cross-sectional view (enlarged view of the portion B indicated by the dashed line in FIG. 3A) showing the state of the interface between the core material and the fiber-reinforced resin layer in the resin composite. [Figure 4] FIG. 4 is a schematic perspective view showing an example of use of a resin composite. [Diagram 5] FIG. 5 is a schematic diagram showing the manufacturing process of a resin composite (preparatory stage for manufacturing a fiber-reinforced resin layer). [Figure 6] FIG. 6 is a schematic diagram showing the steps of producing a resin composite (the stage of producing a fiber-reinforced resin layer). [Figure 7] FIG. 7 is a schematic diagram showing the production process of a resin composite (preparatory stage in producing a resin composite). [Figure 8] FIG. 8 is a schematic diagram showing the steps of producing a resin composite (stages of producing a resin composite). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] A resin composite according to an embodiment of the present invention will be described below. As shown in FIG. 1, the resin composite according to this embodiment is a plate-like body having a longitudinal direction X and a lateral direction Y perpendicular to the longitudinal direction X. The resin composite 100 shown in FIG. 1 has a rectangular shape in a plan view. The rectangle has a long side along the longitudinal direction X and a short side along the lateral direction. The resin composite 100 has a thickness direction Z perpendicular to the longitudinal direction X and the lateral direction Y.
[0009] As shown in FIGS. 1 and 2, the resin composite 100 according to this embodiment has a surface material having a fiber-reinforced resin layer 2 laminated on both sides of a plate-shaped core material 1. In the resin composite 100 according to this embodiment, the surface material is composed of only the fiber-reinforced resin layer 2. The surface material may be provided with a film layer, a coating layer, or the like. In this embodiment, these may be provided outside the fiber-reinforced resin layer 2 to improve the aesthetics of the resin composite 100. The resin composite 100 according to this embodiment has a structure in which the core material 1 is sandwiched between two fiber-reinforced resin layers 2. That is, the resin composite 100 has a first fiber-reinforced resin layer 2a constituting one surface 100a and a second fiber-reinforced resin layer 2b constituting the other surface 100b.
[0010] The core material 1 has one or more sheets of fiber reinforced resin laminated on one side and one or more sheets of fiber reinforced resin laminated on the other side opposite to the one side. As shown in Fig. 3A, in this embodiment, a plurality of sheets of fiber reinforced resin 20 are laminated on each of the one side and the other side of the core material 1. That is, the fiber reinforced resin layer 2 of this embodiment has a laminated structure.
[0011] The two fiber reinforced resin layers 2a, 2b in this embodiment, which are made of a plurality of fiber reinforced resin materials, may have a common structure or may have different structures. The two fiber reinforced resin layers 2a, 2b in this embodiment have a common structure. Each of the fiber reinforced resin layers 2a, 2b has a first surface and a second surface opposite to the first surface, and the first surface is the inner surface of the fiber reinforced resin layers 2a, 2b and serves as an adhesive surface with the core material 1. The second surfaces of the fiber reinforced resin layers 2a, 2b are the outer surfaces of the fiber reinforced resin layers 2a, 2b and serve as one surface 100a and the other surface 100b of the resin composite 100.
[0012] The first fiber reinforced resin layer 2a has a laminated structure in which, for example, five sheets of fiber reinforced resin material 20 are laminated. One surface of the first fiber reinforced resin material 20 (hereinafter, also referred to as "first sheet 21") among the five sheets of fiber reinforced resin material 20 is in contact with the core material 1. That is, the first sheet 21 constitutes an adhesive surface, of the two surfaces of the fiber reinforced resin layer 2, that is adhered to the core material 1.
[0013] The other surface side of the first sheet 21 is in contact with the second fiber reinforced resin material 20 (hereinafter also referred to as the "second sheet 22") of the five fiber reinforced resin materials 20. The third fiber reinforced resin material 20 (third sheet 23), the fourth fiber reinforced resin material 20 (fourth sheet 24), and the fifth fiber reinforced resin material 20 (fifth sheet 25) are laminated in this order, and the fifth sheet 25 is the fiber reinforced resin material 20 provided at the position farthest from the core material 1. That is, the first sheet 21 constitutes the surface opposite to the surface bonded to the core material 1 among the two surfaces of the fiber reinforced resin layer 2. The fifth sheet 25 constitutes one surface 100a of the resin composite 100.
[0014] The second fiber-reinforced resin layer 2b is also the same in that the first sheet 21 is bonded to the core material 1, and the second sheet 22 to the fifth sheet 25 are laminated in this order in the direction away from the core material 1.
[0015] In this embodiment, each of the first fiber reinforced resin layer 2a and the second fiber reinforced resin layer 2b satisfies both of the following formulas (1) and (2), when the tensile modulus in the longitudinal direction X is Ew (GPa) and the tensile modulus in the transverse direction Y is Eh (GPa). 6 ≦ (Ew / Eh) ≦ 20 ···(1) 70 ≦ Ew (2)
[0016] As described above, in the resin composite 100 of this embodiment, in order to strengthen the bending rigidity in the longitudinal direction X, where bending is likely to occur, more than the bending rigidity in the lateral direction Y, the fiber-reinforced resin layer 2 having a larger tensile modulus in the longitudinal direction X than in the lateral direction Y is provided. This makes it possible to avoid using fibers or the like excessively in order to strengthen the bending rigidity in the lateral direction Y in the resin composite 100 of this embodiment, and prevents the weight from becoming heavier than necessary.
[0017] In order to exert the above-mentioned functions, the tensile modulus of elasticity (Ew) in the longitudinal direction X of each of the first fiber reinforced resin layer 2a and the second fiber reinforced resin layer 2b is 70 GPa or more as described above. The tensile modulus of elasticity (Ew) is preferably 90 GPa or more. The tensile modulus of elasticity (Ew) may be 100 GPa or more, 150 GPa or more, or 200 GPa or more. The tensile modulus of elasticity (Ew) is, for example, 500 GPa or less.
[0018] In the resin composite 100 of this embodiment, when the dimension (length) in the longitudinal direction X is Lw (mm) and the dimension (width) in the transverse direction Y is Lh (mm), it is preferable that the ratio (Lw / Lh) of the length (Lw) to the width (Lh) satisfies the following formula (a). 1.5 ≦ (Lw / Lh) (a)
[0019] The ratio (Lw / Lh) may be 2.5 or more, 3.5 or more, or 4.5 or more. The ratio (Lw / Lh) is set to, for example, 20 or less.
[0020] The length (Lw) of the resin complex 100 is preferably 1000 mm or more. The length (Lw) may be 1500 mm or more, or may be 2000 mm or more. The length (Lw) is, for example, 4000 mm or less.
[0021] The width (Lh) of the resin complex 100 is preferably 200 mm or more. The width (Lh) may be 250 mm or more, or 300 mm or more. The width (Lh) may be 400 mm or more.
[0022] When the dimension (thickness) of the resin complex 100 in the thickness direction is Lt (mm), it is preferable that the ratio (Lt / Lw) of the thickness (Lt) to the length (Lw) satisfies the following formula (b). 0.1 ≦ (Lt / Lw) (b)
[0023] The thickness of the resin complex 100 is preferably 15 mm or more. The thickness (Lt) of the resin complex 100 may be 20 mm or more, 25 mm or more, or 30 mm or more. The thickness of the resin complex 100 may be 35 mm or more.
[0024] The length (Cw (mm): dimension in the longitudinal direction X) and width (Ch (mm): dimension in the lateral direction Y) of the core material 1 are the same as those of the resin composite 100. The thickness (Ct (mm)) of the core material 1 is preferably 12 mm or more. The thickness (Ct) of the core material 1 may be 18 mm or more, 23 mm or more, or 28 mm or more. The thickness (Ct) of the core material 1 may be 33 mm or more.
[0025] In this embodiment, surface materials may be provided on the side surfaces of the resin composite 100 so that all six surfaces of the core material 1 are covered with surface materials. In this case, the length (Cw) and width (Ch) of the core material 1 may be smaller than the length (Lw) and width (Lh) of the resin composite 100 by the thickness of the surface materials (fiber-reinforced resin layers).
[0026] The thickness of the fiber reinforced resin layer 2 is preferably 0.40 mm or more. The thickness of the fiber reinforced resin layer 2 may be 0.50 mm or more, 0.60 mm or more, or 0.70 mm or more. The thickness of the fiber reinforced resin layer 2 is, for example, 3.00 mm or less. The thickness of the fiber reinforced resin layer 2 is preferably 2.00 mm or less.
[0027] The dimensions of the resin composite 100, the core material 1, and the fiber reinforced resin layer 2 can be calculated as an arithmetic average of measurements taken at multiple locations (e.g., 4 or 5 locations). For example, the thicknesses of the resin composite 100, the core material 1, and the fiber reinforced resin layer 2 can be calculated as an arithmetic average of four measurements taken at the centers of the four sides of a rectangle.
[0028] In the present embodiment, the core material 1 has a tensile modulus of elasticity Ef (MPa) in the longitudinal direction X and an apparent density D (kg / m 3 ), the following formula (3) is satisfied. 0.5 ≦ (Ef / D) ≦ 1.5 (3)
[0029] The apparent density (D) of the core material 1 is 200 kg / m 3 may be less than 150 kg / m 3 The apparent density (D) of the core material 1 may be 110 kg / m or less. 3 The apparent density (D) of the core material 1 is preferably 100 kg / m or less. 3 More preferably, it is 80 kg / m or less. 3 The apparent density (D) of the core material 1 is preferably 30 kg / m or less. 3 More preferably, it is equal to or greater than this.
[0030] The apparent density (D) of the core material 1 can be determined as the arithmetic average value of the apparent densities of samples cut out from multiple locations (e.g., 4 or 5 locations) of the core material 1. Each sample can be measured, for example, based on the method described in JIS K7222-2005 "Foamed plastics and rubber - Determination of apparent density." Specifically, a 100 cm2 piece cut without changing the original cell structure is 3 For the above test pieces, their volumes (V(m 3 The apparent density can be calculated by measuring the mass (M (kg)) and the volume (V) and calculating the ratio (M / V) of the mass (M) to the volume (V).
[0031] The resin foam constituting the core material 1 may be, for example, an acrylic resin foam, a polystyrene resin foam, a polyester resin foam, or a polycarbonate resin foam. The resin foam may be a foam obtained by in-mold foam molding, or may be a foam obtained by an extrusion method. The foam obtained by in-mold foam molding may be a bead foam molded product obtained by thermally fusing resin foam beads together in a mold, or a block foam molded product obtained by foaming a block of a resin composition containing a foaming agent in a mold.
[0032] The resin foam constituting the core material 1 is preferably an acrylic resin foam. That is, the resin foam is preferably composed of an acrylic resin composition containing an acrylic resin. The acrylic resin foam is preferably a bulk foamed molded product.
[0033] The acrylic resin preferably contains a composition derived from a plurality of polymerizable monomers, such as an acrylic monomer and a monomer copolymerizable with the acrylic monomer.
[0034] Examples of the acrylic monomer include maleic anhydride, methacrylamide, (meth)acrylic acid, methyl methacrylate, maleic acid, fumaric acid, itaconic acid, itaconic anhydride, crotonic acid, methyl acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, lauryl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, acrylamide, maleic acid amide, maleic acid imide, etc. In this specification, the term "(meth)acrylic" is used to mean either "methacrylic" or "acrylic".
[0035] An example of the monomer copolymerizable with the acrylic monomer is a styrene monomer.
[0036] The acrylic resin preferably has 50 to 70% by mass derived from methyl methacrylate, 14 to 27% by mass derived from (meth)acrylic acid, and 10 to 30% by mass derived from styrene. Of the 14 to 27% by mass of (meth)acrylic acid-derived structural units, all may be derived from methacrylic acid or all may be derived from acrylic acid, or both the methacrylic acid-derived structural units and the acrylic acid-derived structural units may be contained in a total amount of 14 to 27% by mass.
[0037] In the case where the structural units derived from maleic anhydride and methacrylamide are contained, it is preferable that 35 to 60 mass% of the structural units are derived from methyl methacrylate, 14 to 35 mass% are derived from (meth)acrylic acid, 10 to 20 mass% are derived from styrene, 1.0 to 10 mass% are derived from maleic anhydride, and 1.0 to 10 mass% are derived from methacrylamide. Maleic anhydride and methacrylamide effectively act to make the acrylic resin exhibit excellent heat resistance. In this case, all of the structural units derived from (meth)acrylic acid contained in a proportion of 14 to 35 mass% may be derived from methacrylic acid or may be derived from acrylic acid, and both the structural units derived from methacrylic acid and the structural units derived from acrylic acid may be contained so that the total amount of the structural units is 14 to 35 mass%.
[0038] The acrylic resin composition may further contain a plasticizer, such as a phthalate ester, an adipate ester, a trimellitate ester, a polyester, a phosphate ester, a citrate ester, an epoxidized vegetable oil, a sebacillate ester, an azelaate ester, a maleate ester, a benzoate ester, or a sulfonate ester.
[0039] Examples of the phthalic acid ester include dioctyl phthalate, diisononyl phthalate, diisodecyl phthalate, dibutyl phthalate, etc. Examples of the adipic acid ester include dioctyl adipate, diisononyl adipate, diisobutyl adipate, dibutyl adipate, etc. Examples of the trimellitic acid ester include trioctyl trimellitate, etc.
[0040] Examples of the phosphate ester include tricresyl phosphate, triamyl phosphate, and tributyl phosphate. Examples of the citrate ester include acetyl phosphate, Examples thereof include tributyl citrate, triethyl citrate, and triethyl acetyl citrate.
[0041] Examples of the epoxidized vegetable oil include epoxidized soybean oil and epoxidized linseed oil.
[0042] The sulfonate esters include alkylsulfonic acid phenyl esters, and commercially available products of the sulfonate esters include Mesamoll manufactured by LANXESS.
[0043] Suitable examples of the plasticizer include dioctyl phthalate, diisobutyl adipate, tributyl acetyl citrate, sulfonate, etc. The plasticizer is preferably contained in an amount of 0.1 to 20 parts by mass, more preferably 0.3 to 10 parts by mass, and particularly preferably 0.5 to 5 parts by mass, relative to 100 parts by mass of the acrylic resin.
[0044] The acrylic resin composition may further contain various additives such as colorants, weathering agents, bio-resistant agents (antibacterial agents, antifungal agents, anti-termite agents, anti-rodent agents, etc.), and fillers.
[0045] In this embodiment, each of the fiber reinforced resin materials 20 from the first sheet 21 to the fifth sheet 25 includes a base sheet made of fiber and a resin impregnated into the base sheet. The base sheet of each of the first sheet 21 and the fifth sheet 25 is made of glass fiber, and the base sheet of each of the second sheet 22 to the fourth sheet 24 is made of carbon fiber.
[0046] The base sheet of this embodiment may be a nonwoven fabric or a woven fabric. The base sheet may be a sheet (UD material) in which fibers are simply aligned in one direction. When the base sheet is a woven fabric, the weave of the woven fabric may be a plain weave, a twill weave, or a satin weave. Examples of the fibers constituting the base sheet include alumina fibers, basalt fibers, rock wool, metal fibers, glass fibers, and carbon fibers. Examples of the fibers constituting the base sheet may be resin fibers such as aramid fibers and polyether ether ketone fibers.
[0047] The resin constituting the fiber reinforced resin material 20 together with the base sheet may be a thermoplastic resin or a thermosetting resin. The resin is preferably a thermosetting resin, which is advantageous in making the fiber reinforced resin material 20 exhibit excellent strength. That is, the fiber reinforced resin layers 2a, 2b of this embodiment are preferably composed of a prepreg sheet containing a base sheet and an uncured thermosetting resin impregnated into the base sheet. Examples of the thermosetting resin include an epoxy resin and an unsaturated polyester resin.
[0048] The substrate sheet of the present embodiment is preferably made of either glass fiber or carbon fiber. The carbon fiber may be a pitch-based carbon fiber or a PAN-based carbon fiber.
[0049] In this embodiment, the first sheet 21 and the fifth sheet 25 constituting both sides of the fiber reinforced resin layers 2a, 2b are made of different materials from the second sheet 22, the third sheet 23, and the fourth sheet 24 provided between them. In this embodiment, the base sheets of the first sheet 21 and the fifth sheet 25 are plain woven fabrics made of glass fiber. On the other hand, the second sheet 22, the third sheet 23, and the fourth sheet 24 are UD materials in which carbon fibers are aligned in one direction.
[0050] The first sheet 21 and the fifth sheet 25 are arranged such that the direction of the glass fibers is parallel to the longitudinal direction X and the lateral direction Y. The second sheet 22, the third sheet 23, and the fourth sheet 24 are arranged such that the direction of the carbon fibers is parallel to the longitudinal direction X. The second sheet 22, the third sheet 23, and the fourth sheet 24 of this embodiment may all have a UD material made of pitch-based carbon fiber as a base sheet, or may all have a UD material made of PAN-based carbon fiber as a base sheet, or any one of them may have a UD material made of pitch-based carbon fiber as a base sheet and another one may have a UD material made of PAN-based carbon fiber as a base sheet.
[0051] When bending stress or the like is applied to the resin composite 100, stress concentration is likely to occur on the outer surfaces of the fiber reinforced resin layers 2a, 2b and on the bonding surface with the core material 1. In this embodiment, the base sheets of the first sheet 21 and the fifth sheet 25 constituting these surfaces are woven fabrics rather than UD materials, so that cracks and the like are less likely to occur on the surfaces of the fiber reinforced resin layers 2a, 2b. Moreover, such effects can be more significantly exhibited by adopting a plain weave fabric as the base sheet of the first sheet 21 and the fifth sheet 25, rather than a woven fabric woven with skipped weft threads and warp threads such as twill weave and satin weave. In order to exhibit such a function, the base sheet of the first sheet 21 and the fifth sheet 25 may not be made of glass fiber, but may be made of carbon fiber.
[0052] In the fiber reinforced resin layers 2a and 2b of this embodiment, by using the UD material, many fibers are used for reinforcement in the longitudinal direction X where bending deformation is likely to occur, and fibers for reinforcement in the lateral direction Y where bending deformation is unlikely to occur are saved. This makes it easy to reduce the weight of the resin composite 100 of this embodiment. The fiber content of each fiber reinforced resin material and the fiber reinforced resin layers 2a and 2b is usually 50% by mass or more. The fiber content may be 55% by mass or more, or 60% by mass or more. The fiber content is, for example, 80% by mass or less. The fiber content may be 75% by mass or less, or 70% by mass or less.
[0053] The fiber content (MF1: mass%) in the first fiber reinforced resin layer 2a and the fiber content (MF2: mass%) in the second fiber reinforced resin layer 2b are preferably approximately the same, and the ratio (MF1 / MF2) between them is preferably 0.8 to 1.25. Of the multiple fiber reinforced resin materials 20 constituting each of the fiber reinforced resin layers 2a and 2b, the fiber content (PF1: mass%) in the fiber reinforced resin material 20 with the lowest fiber content and the fiber content (PF2: mass%) in the fiber reinforced resin material 20 with the highest fiber content are preferably approximately the same, and the ratio (PF1 / PF2) between them is preferably 0.8 to 1.25.
[0054] The fiber weight per unit area of the first fiber-reinforced resin layer 2a (QF1: g / m 2 ) and the fiber basis weight (QF2: g / m 2 Similarly, it is preferable that the ratio of the two (QF1 / QF2) is 0.8 to 1.25. The fiber weight (RF1: g / m2) of the fiber reinforced resin material 20 having the smallest fiber weight among the plurality of fiber reinforced resin materials 20 constituting each of the fiber reinforced resin layers 2a and 2b is preferably about the same. 2 ) and the fiber weight (RF2: g / m 2 ) are preferably approximately the same, and the ratio between them (RF1 / RF2) is preferably 0.8 to 1.25.
[0055] For the reasons described above, resin composite 100 of the present embodiment is configured so as to satisfy formula (1) and formula (2).
[0056] In the resin composite 100 of this embodiment, the resin of the fiber reinforced resin material 20 is impregnated into the core material 1, which provides even greater strength. In the resin composite 100 of this embodiment, the resin of the fiber reinforced resin material 20 is impregnated into the core material 1, which not only provides excellent adhesive strength between the fiber reinforced resin layer 2 and the core material 1 due to the anchor effect, but also makes it possible to suppress stress concentration at the interface between the fiber reinforced resin layer 2 and the core material 1 when bending stress is applied.
[0057] In this embodiment, instead of impregnating with the resin of the fiber reinforced resin material 20, the same effect can be obtained by bonding the fiber reinforced resin layer 2 and the core material 1 with an adhesive and impregnating the core material 1 with the resin contained in the adhesive. The resin to be impregnated into the core material 1 is preferably an epoxy resin, an unsaturated polyester resin, a polyurethane resin, an acrylic resin, or the like.
[0058] As shown in FIG. 3B, the core material 1 has a permeation region 11 in which the resin of the fiber reinforcement 20 permeates deeper than the surface 1a of the core material 1 at a portion constituting the interface XS with the fiber reinforced resin layer 2. That is, in the resin composite body 100 of this embodiment, the resin seeps out from the fiber reinforced resin layer 2 and permeates into the core material 1. The core material 1 of this embodiment has a non-permeation region 12 in which the resin does not permeate inside the permeation region 11. That is, the core material 1 has the permeation region 11 at both ends in the thickness direction Z of the resin composite body 100, and the non-permeation region 12 in the middle of the permeation region 11. In the figure, the permeation region 11 is shown to be formed along the short-side direction Y of the resin composite body 100, but the permeation region 11 also has an extension in the longitudinal direction X of the resin composite body 100.
[0059] The permeation region 11 is preferably formed so that the depth DP from the interface XS is as uniform as possible, and preferably has a large area as viewed in the thickness direction of the resin composite body 100. The area of the interface XS where the core material 1 and the fiber reinforced resin layer 2 come into contact is defined as S0 (cm 2 ), and the area of the permeation region 11 is S1 (cm 2 ), it is preferable that the area ratio (S1 / S0) satisfies the following relational expression (X1). 80% ≦ (S1 / S0)×100% (X1)
[0060] The area ratio (S1 / S0) more preferably satisfies the following relational formula (X2), and particularly preferably satisfies the following relational formula (X3). 85% ≦ (S1 / S0)×100% (X2) 90% ≦ (S1 / S0)×100% (X3)
[0061] The permeation region 11 into which the resin has permeated preferably has a maximum depth (maximum depth in a direction perpendicular to the interface) of 500 μm or more from the interface XS between the core material 1 and the fiber-reinforced resin layer 2. The area of the portion into which the resin has permeated by 500 μm or more from the interface XS is defined as S2 (cm 2 ), it is preferable that the area ratio (S2 / S0) of the area to the interface satisfies the following relational expression (X4). 5% ≦ (S2 / S0)×100% (X4)
[0062] The area ratio (S2 / S0) more preferably satisfies the following relational formula (X5), and particularly preferably satisfies the following relational formula (X6). 10% ≦ (S2 / S0)×100% (X5) 20% ≦ (S2 / S0)×100% (X6)
[0063] The average depth of the portion penetrated by the resin is preferably 200 μm or more, more preferably 350 μm or more, and particularly preferably 500 μm or more.
[0064] The average depth of the portion into which the resin has permeated can be obtained by determining the cross-sectional area (Sa) of the portion into which the resin has permeated in a section of a certain length (L) in the direction along the interface XS in a cross section that appears by cutting the resin composite 100 in a direction perpendicular to the interface XS, and dividing this cross-sectional area (Sa) by the length (L).
[0065] The permeation region 11 is preferably in the above-described state at a location where either the first fiber reinforced resin layer 2a or the second fiber reinforced resin layer 2b is laminated, and more preferably in the above-described state at both the first fiber reinforced resin layer 2a and the second fiber reinforced resin layer 2b.
[0066] The resin composite 100 of this embodiment may be used by being attached to a frame material 200 for reinforcement, as shown in Fig. 4. For example, by attaching a frame material 200 that covers four faces of the resin composite 100, including sides parallel to the longitudinal direction X and sides parallel to the lateral direction Y, and that has a rectangular frame-like side wall portion 201 whose dimension in the thickness direction Z is slightly larger than that of the resin composite 100, and flange portions 202 that extend inwardly from both the upper and lower ends of the side wall portion 201 by a short distance so as to follow the outer faces of the fiber reinforced resin layers 2a and 2b, deformation of the resin composite 100 can be further suppressed.
[0067] When the frame material 200 is made of metal, it is preferable to insert an electrically insulating intervening material so that the end face of the carbon fiber base sheet does not directly contact the frame material 200. The intervening material may be something like paint or adhesive tape, or it may be something like an adhesive. This can prevent galvanic corrosion and the like from occurring in the frame material 200.
[0068] That is, the resin composite 100 of this embodiment can be used as a constituent member of a plate-shaped member having a plate-shaped resin composite and a frame material covering the outer periphery of the resin composite 100, and in the plate-shaped member, the frame material may be made of metal, and when carbon fibers are contained in the fiber-reinforced resin layer of the resin composite, the carbon fibers and the frame material may be electrically insulated.
[0069] The resin composite 100 of this embodiment and a plate-like member containing the resin composite 100 are excellent in light weight and strength and can be used in various applications. The resin composite 100 and the plate-like member of this embodiment can be used in various applications, such as mobile body applications such as the bodies of trucks and ships and containers mounted on railway cars, building material applications such as wall panels, floor panels, and ceiling panels, civil engineering applications such as retaining walls and waterstops that block the entrances and exits of waterways and embankments, and housings for large equipment.
[0070] The uses of the resin composite 100 of this embodiment are not limited to the above examples. Furthermore, the resin composite 100 of this embodiment is not limited to the above examples, and various modifications may be made. That is, the present invention is not limited to the above examples. EXAMPLES
[0071] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these.
[0072] First, four types of prepreg sheets shown in Table 1 below were prepared as materials for forming the fiber reinforced resin layer. [Table 1]
[0073] Example 1 A fiber-reinforced resin material (thickness: 0.22 mm, basis weight: 280 g / m) was prepared by impregnating a base sheet of unidirectionally aligned carbon fibers with 32% by mass of uncured epoxy resin. 2Four sheets of fiber reinforced resin (Dialead Prepreg HYEJ28M80QD manufactured by Mitsubishi Chemical Corporation, Fiber Reinforced Resin Material 1 in Table 1) were cut to arbitrary dimensions (2450 mm x 525 mm) and prepared. The fiber reinforced resin was cut so that the longitudinal direction was the direction in which the fibers were aligned.
[0074] A fiber-reinforced resin material (thickness: 0.17 mm, basis weight: 315 g / m) in which 33% uncured epoxy resin is impregnated in a base sheet made of plain woven glass fiber. 2 Four sheets of fiber reinforced resin material (Rikalight EGP87 LA18BR manufactured by Nippon Rika Co., Ltd., and Fiber Reinforced Resin Material 2 in Table 1) were cut to arbitrary dimensions (2450 mm x 525 mm) and prepared. The prepared fiber reinforced resin materials were laminated while matching the outer peripheral edges according to the lamination configuration described in Table 2, to produce laminates 1-1 and 1-2 composed of multiple fiber reinforced resin materials.
[0075] [Table 2]
[0076] Next, one aluminum plate with a thickness of 4 mm (dimensions: 2550 mm × 625 mm, hereinafter referred to as "aluminum plate 1") and three aluminum plates with a thickness of 3 mm (dimensions: 2450 mm × 525 mm, hereinafter referred to as "aluminum plates 2-1, 2-2, 2-3") were prepared, and a release agent ("Kemlease 2166" manufactured by Chemlease Japan) was applied to the upper surface of aluminum plate 1 and left for one day to subject the upper surface of aluminum plate 1 to a release treatment. Note that no release treatment was applied to the outer periphery of the upper surface of aluminum plate 1, in order to place a sealant and a back valve, which will be described later.
[0077] Next, as shown in Figure 1, an aluminum plate 1 (AL1) with a release treatment on the upper surface was used as a base plate, and an aluminum plate 2-1 (AL2-1), a release film (SP) (dimensions: 2500 mm x 575 mm, "Torayfan YM17S" manufactured by Toray Industries, Inc., thickness: 25 μm, release surface: matte finish), and laminates 1-1 and 1-2 (LB1-1 and LB1-2) were stacked as shown in Figure 5 to produce a secondary laminate (LB2). The protruding release film (SP) was fixed to the side of the secondary laminate (LB2) with masking tape to prevent excessive resin from flowing out of the laminates 1-1 and 1-2 (LB1-1 and LB1-2). As shown in FIG. 5, aluminum plate 2-1 (AL2-1), aluminum plate 2-2 (AL2-2), and aluminum plate 2-3 (AL2-3) were used as pressing members, and a secondary laminate (LB2) was produced by sandwiching laminates 1-1 and 1-2 (LB1-1 and LB1-2) between each pressing member and a release film (SP).
[0078] Thereafter, a breather cloth (BC) (AIRTECH's "AIRWEAVE N4") was placed on the secondary laminate (LB2) to completely cover the secondary laminate (LB2). A bagging film (BF) (AIRTECH's "WL7400") was placed on the breather cloth (BC), and the outer periphery of the bagging film (BF) was bonded to the opposing base plate (aluminum plate 1 (AL1)) using a sealant (SL) (AIRTECH's sealant tape "GS43MR"). The secondary laminate (LB2) was sealed with the bagging film (BF) to produce a laminate structure (LBX) as shown in FIG. 6. The bagging film (BF) was made of nylon film, and a back valve (BB) (AIRTECH's "VACVALVE 402A") was placed on a part of it.
[0079] Next, the laminated structure (LBX) was fed into the autoclave, the back valve (BB) of the laminated structure (LBX) was connected to a vacuum line, and the space sealed with the bagging film (BF) was depressurized to a vacuum degree of 0.10 MPa. The depressurization of the space was continued thereafter. Thereafter, the laminated structure (LBZ) was heated so that its surface temperature reached 130°C and held for 180 minutes, and the secondary laminate (LB2) was pressed in the thickness direction at a pressure of 0.3 MPa to harden the epoxy resin. Thereafter, the secondary laminate (LB2) was cooled to 60°C, and the fiber-reinforced resin layers 1-1 and 1-2 formed by the laminates 1-1 and 1-2 (LB1-1 and LB1-2) were taken out of the autoclave. The thickness of the fiber-reinforced resin layer was 0.78 mm.
[0080] (Preparation of Foam) A monomer solution containing a monomer such as a (meth)acrylic acid ester (A), (meth)acrylic acid (B), and styrene (C) and a blowing agent (urea) was bulk polymerized, and the polymer was heated and foamed to obtain a bulk foamed molded product, from which a plate-shaped resin foam (resin foam 1) was cut out.
[0081] (Adhesion process) Resin foam 1 (FB1) (acrylic resin foam, dimensions: 2450 mm x 525 mm, thickness: 39.4 mm, Sekisui Chemical Co., Ltd. "Formac S#2000", apparent density: 56 kg / m 3), and as a room temperature curing adhesive, epoxy resin ("EPOXY RESIN AW136N" manufactured by Nagase Elex Co., Ltd.) and hardener ("HARDENER HY994" manufactured by Nagase Elex Co., Ltd.) were prepared. 227 g of epoxy resin and 91 g of hardener were measured out using a weighing scale, and they were mixed uniformly to prepare epoxy adhesive (EPX), which was then applied to one side of fiber reinforced resin layer 1-1 (FRP1-1) with a spatula so that the thickness was uniform. Epoxy adhesive (EPX) was also applied to one side of fiber reinforced resin layer 1-2 (FRP1-2) in the same manner. A resin foam 1 (FB1) was sandwiched between fiber reinforced resin layers 1-1 (FRP1-1) and 1-2 (FRP1-2) to which epoxy adhesive (EPX) was applied, to produce a tertiary laminate (LB3). Next, the tertiary laminate (LB3) was sandwiched between an aluminum plate 1 (AL2-1) and a release film (SP) to produce a quaternary laminate (LB4) as shown in Figure 7. The protruding release film (SP) was fixed to the side of the quaternary laminate (LB4) with masking tape to prevent the adhesive from flowing out excessively from the quaternary laminate (LB4).
[0082] Thereafter, as shown in Fig. 8, the quaternary laminate (LB4) was entirely wrapped in a breather cloth (BC) and further wrapped in a cylindrical bagging film (BF), and the ends of the bagging film (BF) were joined with a sealant tape (SL), and the quaternary laminate (LB4) was sealed with the bagging film (BF) to produce a secondary laminate structure (LBY). A back valve (BB) was placed in a part of the bagging film (BF).
[0083] Next, the secondary laminated structure (LBY) was fed into the autoclave, the back valve (BB) of the secondary laminated structure (LBY) was connected to a vacuum line, and the space sealed with the bagging film (BF) was depressurized to a vacuum of 0.10 MPa. The depressurization of the space was continued thereafter. Thereafter, the secondary laminated structure (LBY) was heated so that its surface temperature reached 80°C, and was held for 60 minutes to harden the epoxy adhesive (EPX). Thereafter, the secondary laminated structure (LBY) was cooled to 60°C, and the integrated fourth laminate (LB4) was taken out of the autoclave as a resin composite. The thickness of the resin composite was 41.0 mm.
[0084] (Measurement method) (Thickness of fiber reinforced resin layer) Using a digital caliper (manufactured by Mitutoyo Corporation, product name "Digimatic Caliper"), measurements were taken near the midpoints of the four sides of the rectangle, and the average value was calculated.
[0085] (Tensile modulus of fiber-reinforced resin layer) The tensile modulus was measured in accordance with JIS Z2241. In other words, the tensile modulus was measured using an "AG-100KNE type autograph tensile tester" manufactured by Shimadzu Corporation. The test pieces were cut out in a dumbbell shape of JIS 13B size for each direction, with the fiber direction of the UD material being the 0° direction (longitudinal direction of the resin composite) and the direction perpendicular to the fiber direction being the 90° direction (transverse direction of the resin composite). The number of test pieces was 5 for each direction. The test pieces were conditioned for 16 hours under the standard atmosphere of JIS K 7100:1999 symbol "23 / 50", class 2, and then used for measurement. The measurement was performed under the same environment, and the test speed was 1 mm / min. From the obtained graph, the load region where the slope was maximum was set, and the tensile modulus of elasticity of the fiber reinforced resin layer in the longitudinal direction (Ew) and the tensile modulus of elasticity of the fiber reinforced resin layer in the transverse direction (Eh) were obtained by the universal testing machine data processing.
[0086] (Thickness of resin foam) The thickness of the resin foam was measured using a digital caliper (manufactured by Mitutoyo Corporation, product name "Digimatic Caliper"). The measurement was performed near the midpoints of the four sides of a rectangle. The thickness of the resin foam was calculated by arithmetically averaging the measured values.
[0087] (Tensile modulus of resin foam) The tensile modulus of the resin foam in the longitudinal direction was measured in accordance with JIS K6767:1999. That is, the tensile modulus was measured using Shimadzu Corporation's "Autograph AG-X plus 100kN" universal testing machine and Shimadzu Corporation's "TRAPEZIUM X" universal testing machine data processing. The test pieces were cut out to be dumbbell-shaped type 1 (ISO1798 stipulation) with a thickness of 11 mm. The number of test pieces was 5. The test pieces were conditioned for 16 hours under the standard atmosphere of JIS K 7100:1999 symbol "23 / 50" and class 2, and then used for measurement. The measurement was performed under the same environment, with a test speed of 500 mm / min and a grip interval of 100 mm. From the obtained graph, the load region with the maximum slope was set, and the tensile modulus was obtained by the universal testing machine data processing.
[0088] (Apparent density of resin foam) The apparent density was calculated by the following formula. Apparent density (kg / m 3 ) = Resin foam mass (kg) / Resin foam size (m 2 ) / resin foam thickness (m)
[0089] (Thickness of resin composite) The thickness of the resin composite was measured using a digital caliper (manufactured by Mitutoyo Corporation, product name "Digimatic Caliper"). The measurements were performed near the midpoints of the four sides of the rectangle. The thickness of the resin composite was calculated by arithmetically averaging the measured values.
[0090] (Deflection of resin composite) The deflection of the resin composite was measured using an Instron Universal Testing Machine Model 5982. The test pieces were cut out to a width of 82 mm, length of 920 mm, and thickness of 41 mm so that the 0° direction was the longitudinal direction when the fiber direction of the unidirectional fiber reinforcement (the longitudinal direction of the resin composite) was set as the 0° direction. Five test pieces were used. The test pieces were conditioned for 16 hours under a standard atmosphere of JIS K 7100:1999 symbol "23 / 50", class 2, and then used for measurement. The measurements were performed under the same environment, with a test speed of 5 mm / min. The radius of the tip of the pressure wedge and the fulcrum was 5R, and the distance between the fulcrums was 820 mm. From the obtained load-displacement curve, the deflection of the center of the panel when a load of 500 N was applied was measured.
[0091] (Apparent density of resin composite) The apparent density of the resin composite was calculated using the following formula. Apparent density of resin composite (kg / m 3 ) = Resin foam mass (kg) / Resin composite volume (m 3 )
[0092] (Evaluation Criteria) The deflection of the resin composite is 2.5mm or less, and the apparent density of the resin composite is 180kg / m 3 The following resin composites were judged to have good bending rigidity and light weight.
[0093] (Examples 2 to 6, Comparative Examples 1 and 2) The resin composites of Examples 2 to 6 and Comparative Examples 1 and 2 were molded in the same manner as in Example 1, except that the laminate structure and the resin foam were changed as shown in Table 2. These resin composites were evaluated in the same manner as in Example 1. The results are also shown in Table 2. In Comparative Example 1, in addition to changing the resin foam, the temperature in the bonding process was changed to 40°C and the retention time to 8 hours. The foam in Example 4 (resin foam 2) was composed of the same acrylic resin composition as the foam in Example 1 (resin foam 1), except that it had a different expansion ratio. The foam (resin foam 3) in Comparative Example 1 is a bead foam molded product made of polystyrene resin.
[0094] From the above, it is clear that the present invention can provide a resin composite having excellent light weight and bending rigidity. [Explanation of symbols]
[0095] 1: Core material 2: Fiber-reinforced resin layer 20(21,22,23,24,25): Fiber reinforced resin material 100: Resin composite X: Longitudinal direction Y: Short side Z: Thickness direction
Claims
1. A core material and a surface material covering the core material, The core material is made of a resin foam, The surface material is a resin composite including a fiber reinforced resin layer composed of a sheet-shaped fiber reinforced resin material containing resin and fiber, A plate-like body having a longitudinal direction and a lateral direction perpendicular to the longitudinal direction, The tensile modulus of the fiber reinforced resin layer in the longitudinal direction is Ew (GPa), The tensile modulus of the fiber reinforced resin layer in the short direction is Eh (GPa), The tensile modulus of the core material in the longitudinal direction is Ef (MPa), The apparent density of the core material is D (kg / m 3 ) and A resin composite satisfying all of the following formulas (1), (2), and (3): 6 ≦ (Ew / Eh) ≦ 20 ... (1) 70≦Ew...(2) 0.5≦(Ef / D)≦1.5...(3)
2. 2. The resin composite according to claim 1, wherein the fibers are glass fibers or carbon fibers.
3. The resin composite according to claim 1 or 2, wherein the fiber-reinforced resin layer has a thickness of 0.40 mm or more and 2.00 mm or less.
4. The resin composite according to claim 1 , wherein the resin foam is composed of an acrylic resin composition containing an acrylic resin.
5. The apparent density of the core material is 30 kg / m 3 More than 110kg / m 3 The resin composite according to any one of claims 1 to 4, wherein:
Citation Information
Patent Citations
Fiber reinforced resin composite material
JP1995040490A
Carrying member
JP2000343476A
Fiber reinforced composite and method for producing the same
JP2014208418A
Skin coated foam forming particle molded body
JP2018172522A
Fiber composite
JP2019001004A